Pregnancy Complicated by Maternal MODY 3 and Paternal MODY 2 Diabetes and Subsequent Rapidly Falling Insulin Requirement - Anastasia Mikuscheva; Adel Mekhail; Benjamin J. Wheeler (Case Reports in Obstetrics and Gynecology)
Background. ‘Maturity-Onset Diabetes of the Young’ (MODY) or monogenic diabetes accounts for approximately 1–2% of diabetes and is frequently misdiagnosed as type 1 or type 2 diabetes. Here we report a case of a 19-year-old pregnant woman with a MODY 3 diabetes expecting a child to a father with MODY 2 diabetes. Possible inheritance scenarios are described and the implications of these scenarios on the pregnancy and infant are discussed. In addition, the pregnancy was complicated by drastically falling insulin requirements in the mother in the 3rd trimester as well as preterm labour and delivery at 33+4 weeks of gestation.